Student Activities in Animal Structure Practicum Activities Using Modified Free Inquiry-Based Practicum Guidelines - Nurhadi; Mimin Mardhiah Zural; Yuzarion Zubir; Evrialiani Rosba (Jurnal Penelitian Pendidikan IPA, 2023)
Practical work guide of Animal Structure using modified free inquiry is designed so that the practitioner is actively able to solve problems through observation, exploration, and practical work procedures. This research uses the Four-D model (Define, Design, Develop, and Disseminate) developed by Thiagarajan, Semmel, and Semmel (1974). In this research, the validity of the practical work guide has been carried out, and then development tests are carried out by looking at student activities in practical work activities using the practical work guide of Animal Structure using modified free inquiry, observed by observers using observation sheets of attitude and skill. The data was processed using the percentage formula proposed and obtained the value of student attitudinal activity 81.65 (very effective) and student skill activity 80.81 (very effective). Thus, it can be concluded that the practical work guide of Animal Structure using modified free inquiry is very effective to bring up scientific attitude activities and student work skills in practical work activities.